Syncope as the Initial Manifestation of Advanced Nasopharyngeal Carcinoma: A Case Report - Zhang, Si-Cheng; Lin, Mao-Qing; Zhang, Li-Wei; Lin, Xue-Qin; Luo, Man-Qing; Lin, Kai-Yang; Guo, Yan-Song (Frontiers in Cardiovascular Medicine, 2022)
Carotid sinus syndrome is a principal cause of syncope in the elderly. Syncope, associated with carotid sinus syndrome which is secondary to metastasis of advanced nasopharyngeal carcinoma, rarely occurs. The current study reported a 66-year-old woman, who presented with a history of frequent and recurrent syncope as the initial symptom, and was eventually diagnosed with advanced nasopharyngeal carcinoma. The positron emission tomography scan demonstrated a diagnosis of advanced nasopharyngeal carcinoma with involvement in carotid sheath space, and nasopharyngeal biopsy revealed non-keratinized nasopharyngeal carcinoma. After diagnosis and treatment, the patient had no recurrence of syncope. In summary, our case study suggests that great importance should be attached to potential intrinsic causes of syncope especially in the case of nasopharyngeal carcinoma, as it is an insidious malignancy which needs to be precisely identified.